Digital culture in the light of educational processes. Ad vocem for the remarks and musings of Jordan Shapiro concerning the digital childhood - Łukasz Androsiuk; Małgorzata Obrycka (Studia z Teorii Wychowania)
Digital technologies not only reshape the ways we experience the world but also redefine intergenerational relationships and fundamental educational mechanisms. Their presence in educational and upbringing processes brings both new pedagogical opportunities and challenges related to the algorithmization of knowledge, content personalization, and the impact of digital infrastructures on media literacy. While we acknowledge that pedagogical reflection cannot remain indifferent to these processes, we argue that one of its key challenges is maintaining critical balance—resisting both techno-optimistic and techno-phobic perspectives. The aim of this article is to analyze Jordan Shapiro’s concept of digital childhood and to critically engage with some of its fundamental assumptions. While the authors share the conviction that digital culture plays a crucial role in both institutional and non-institutional education, they emphasize, more than Shapiro does, its structural conditions, including algorithmic control mechanisms and the commercialization of educational processes. The adopted method of analytical hermeneutics allows not only for a critical examination of Shapiro’s ideas but also for a reflection on the language used to describe digital education and media culture. The primary research question takes the following form: Does digital childhood, as conceptualized by Jordan Shapiro, still represent a clear opportunity for the development of educational competencies, or does it now require deeper critical reflection particularly in the context of cultural algorithmization and the surveillance capitalism intertwined with it?